Spectrum of congenital anomalies of neonates in a tertiary care hospital in Southern India - Tenali, Ananya S. L.; Kamalakannan, Santosh K.; Jayaraman, Kumutha K. (International Journal of Contemporary Pediatrics, 2018)
Background: Congenital anomalies contribute upto 11% of neonatal deaths globally. Neonates with multiple congenital malformations present a very difficult challenge to the treating physicians. This study was done to know the frequency, pattern of congenital anomalies and various presentations, which may help to develop strategies for patient counseling and management in our setting. Methods: Retrospective hospital based observational study from the period of June 2015 to June 2017. Neonates born in our hospital during the study period with documented congenital anomalies were included in the study and the data was classified as per European Surveillance of Congenital Anomalies and further analysed. Results: Total number of neonates with documented congenital anomalies was 40, of which 6 neonates (15%) had multiple anomalies. The anomalies in the study were divided into major and minor anomaly groups. 70% of the anomalies were classified as major anomalies while 30% were classified as minor anomalies. Multiparity and GDM were found to be major risk factors in the mother. Major anomalies identified involved the Musculoskeletal system (21.6%) and cardiovascular system (20%). Minor anomalies included skin disorders (27.7%) followed by Musculoskeletal (16.6%) and genitourinary system (16.6%). Of the 40 anomalous babies five babies expired soon after birth Conclusions: Antenatal screening is an effective tool to detect Musculoskeletal and CNS anomalies. CVS anomalies may be missed by routine anomaly scan. Early intervention and effective follow up have shown that good outcomes are possible even in while managing some of the major anomalies.